Deviation of polarity from linearity in liquid mixtures containing an ionic liquid - Beniwal, Vijay; Shukla, Shashi K.; Kumar, Anil (Physical Chemistry Chemical Physics, 2015)
The physico-chemical properties of liquid mixtures, in general, exhibit deviations from linear behaviour with respect to their composition, arising out of different types of cross-intermolecular interactions (both specific and non-specific). These specific and non-specific interactions can however be monitored to obtain the linear mixing in liquid mixtures using the pseudo-solvent methodology in such a manner that the interactions causing deviations from linearity are cancelled out and mixtures display linear behaviour.